Power System Engineering: Planning, Design, and Operation of Power Systems and Equipment - Schlabbach, Juergen; Rofalski, Karl-Heinz (John Wiley & Sons, Incorporated, 2014)
With its focus on the requirements and procedures of tendering and project contracting, this book enables the reader to adapt the basics of power systems and equipment design to special tasks and engineering projects, e.g. the integration of renewable energy sources.